Prevalence and association of HIV and tuberculosis status in older adults in South Africa: an urgent need to escalate the scientific and political attention to aging and health - Akokuwebe, Monica Ewomazino; Osuafor, Godswill Nwabuisi; Idemudia, Erhabor Sunday (Frontiers in Public Health, 2024)
Objectives This study examined the prevalence and sociodemographic factors among older adults with HIV and TB status in South Africa. Methods This data was cross-sectional and obtained from the 2019 General Household Surveys in South Africa. Adults 50 years and over with reported HIV and TB status were included (N = 9,180,047). We reported statistical analyses of the descriptive, Chi-square and Fisher’s exact tests, and binary logistic regression. Results The study has found a prevalence rate of HIV to be 5.3% and TB to be 2.9% among older adults aged 50 years and above in South Africa. However, the study found HIV and TB to be highest among older adults residing in Gauteng, KwaZulu-Natal and Eastern Cape provinces. For HIV status, the female gender [AOR = 0.80*, CI 95% = 0.80–0.80] and secondary education [AOR = 0.57, CI 95% = 0.56–0.58] have lower odds of association among older adults with HIV. Regarding TB status, primary education [AOR = 1.08*, CI 95% = 1.06–1.10] and diabetes [AOR = 1.87*, CI 95% = 1.82–1.91] have lower likelihoods of associations among older adults with TB. Conclusion There is an urgent need to escalate scientific and political attention to address the HIV/TB burden in older adults and, public health policymakers need to take cognizance of the interdependence of inequality, mobility, and behavioural modification among this high-risk population.